The right to access to information for users with special needs and dissabilities - Lasić-Lazić, Jadranka (Array, 2004)
In the information society the right to access information is a must. Ensuring equal access to information for all is one of library's missions. People with special needs and dissabilities make between 15 to 25% of the population of the countries through the world. The majority of these people are not library users because libraries do not ensure services adapted to their special needs. Many of them need assistive technologies to access information. The advance of the digital information and the Internet together with the development of more and more sophisticated assistive technologies has helped promote these issues more than ever before. For example, blind and visually impaired people do not need to wait for a book to be produced in Braille, which is very slow and expensive process. Less than 15% of the published books per year in some of the most developed countries of the world ever make into Braille. The digital information can easily be accessible via speech synthesis software, which reads aloud everything that is on the computer screen. In Croatia, a digital collection for students with special needs and disabilities has been created at the Faculty of Philosophy, University of zagreb in cooperation with the Croatian Association for the Blind. For each publication a contract with copyright owners needs to be signed. A new dreaft of the copyright law is being composed, which will hopefully include an exemption for people with special needs and disabilities and thus create an opportunity for making a step towards the democratci information society.